PRICING STRATEGIES FOR PERFORMING ARTS: A THEORETICAL PERSPECTIVE - Thomas, Rani Maria (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the various pricing strategies for performing arts. The traditional pricing strategies focus more on tangible goods that differ from services in many respects. Even in the service category, performing arts have a unique place. The reasons for this uniqueness are explained in this paper. Innovative pricing methods are extensively used in modern times. The study compares traditional, dynamic, and innovative pricing strategies for performing arts. The study suggests that there is no single strategy for any performing art. It varies with time, quantity and quality of audience, place, duration of performance, degree of competition, brand image, etc.